The Clinical Trials of Mesenchymal Stromal Cells Therapy - Mohammad Reza Kouchakian; Neda Baghban; Seyedeh Farzaneh Moniri; Mandana Baghban; Shabnam Bakhshalizadeh; Vahid Najafzadeh; Zahra Safaei; Safoura Izanlou; Arezoo Khoradmehr; Iraj Nabipour; Reza Shirazi; Amin Tamadon (Stem Cells International)
Mesenchymal stromal cells (MSCs) are a heterogeneous population of adult stem cells, which are multipotent and possess the ability to differentiate/transdifferentiate into mesodermal and nonmesodermal cell lineages. MSCs display broad immunomodulatory properties since they are capable of secreting growth factors and chemotactic cytokines. Safety, accessibility, and isolation from patients without ethical concern make MSCs valuable sources for cell therapy approaches in autoimmune, inflammatory, and degenerative diseases. Many studies have been conducted on the application of MSCs as a new therapy, but it seems that a low percentage of them is related to clinical trials, especially completed clinical trials. Considering the importance of clinical trials to develop this type of therapy as a new treatment, the current paper is aimed at describing characteristics of MSCs and reviewing relevant clinical studies registered on the NIH database during 2016-2020 to discuss recent advances on MSC-based therapeutic approaches being used in different diseases.